2011
DOI: 10.1007/s10897-011-9387-4
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent Use of Cultural Health Practices and Western Medicine During Pregnancy: Exploring the Mexican Experience in the United States

Abstract: The relationship between concurrent use of cultural health practices and Western medicine during pregnancy by women of Mexican origin is relatively unstudied. The aim of this study was to explore how cultural health practices are balanced with the use of Western medicine during pregnancy by women of Mexican origin across differing acculturation levels. A convenience sample of 15 women of self-identified Mexican origin between the ages of 18-65 participated either in a telephone interview or one of two small gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
26
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(29 citation statements)
references
References 17 publications
(17 reference statements)
3
26
0
Order By: Relevance
“…As discussed, lihi refers to maternal cravings and this usually occurs during the first trimester of pregnancy (Jocano 1973). This is similar with antojos, a Mexican belief during pregnancy wherein an infant may be born with some characteristics based on the object of maternal cravings (Barragan et al 2011). …”
Section: Lihisupporting
confidence: 66%
See 4 more Smart Citations
“…As discussed, lihi refers to maternal cravings and this usually occurs during the first trimester of pregnancy (Jocano 1973). This is similar with antojos, a Mexican belief during pregnancy wherein an infant may be born with some characteristics based on the object of maternal cravings (Barragan et al 2011). …”
Section: Lihisupporting
confidence: 66%
“…For example, when a genetic condition appears to have no apparent cause, the patient and the family may resort to use these beliefs as a form of rationalization to explain why they are affected. This is also illustrated in the study of Barragan et al (2011) where they suggested that cultural health practices may help patients comprehend and make sense of a disease condition that is otherwise overwhelming, and to have a perceived sense of control of the eventual outcomes of the condition. Sometimes, patients may also resort to these beliefs because these offer an explanation that is external to them which is easier to accept rather than to resort to an explanation that is internal to them (i.e., genetic mutation).…”
Section: Implications In Genetic Counselingmentioning
confidence: 97%
See 3 more Smart Citations